PENDAFTARAN TАNАH SISTEMАTIS LENGKАP (PTSL) DI DESA DONOWARIH, KABUPATEN MALANG - Febry Chrisdanty (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2021)
The Government's program to speed up the land registration process through the Complete Systematic Land Registration (PTSL) is an effort to accelerate the provision of legal protection for land rights while also providing legal certainty for owners. This study aims to analyze the obstacles and also the supporters of the implementation of PTSL in Donowarih Village, Malang Regency. The research method used is empirical research, with a sociological research approach. The results of the study indicate that the implementation of PTSL in Donowarih Village as a whole from stage to stage has been carried out well and runs according to the procedure, but the implementation of PTSL in addition to having supporting factors there are also several things that become obstacles / obstacles in its implementation, namely obstacles that comes from PTSL object, PTSL subject, PTSL implementing HR in the field. and constraints related to its implementation related to PTSL object files. Keywords: Implementation, PTSL, Obstacles.